Oncological and surgical outcomes of radical surgery in elderly colorectal cancer patients with intestinal obstruction - Ma, Qingbiao; Li, Hongyu; Jiang, Yujuan; Wang, Yingfei; Liang, Jianwei (Frontiers in Surgery, 2023)
Background: The treatment strategy for elderly colorectal cancer patients with intestinal obstruction remains controversial. The choice of reasonable treatment and surgical method directly affects perioperative safety and prognosis. This study investigated the safety and long-term efficacy of radical surgery in elderly colorectal cancer patients over 80 years old with intestinal obstruction. Methods: The clinicopathological data of elderly patients over 80 years old with intestinal obstruction who underwent colorectal cancer surgery from January 2012 to December 2021 were retrospectively collected and analysed. Patients were assigned to a radical group and a palliative group according to the surgical method. Propensity score matching (PSM) was performed to match patients in the radical group 1:1 with those in the palliative group. The perioperative-related indexes and prognosis were compared between the two groups. Results: A total of 187 patients were enrolled in this study. After PSM, 58 matched pairs were selected, and the radical and palliative groups were well balanced in terms of the clinical and surgical characteristics (P > 0.05). The proportion of patients transferred to the ICU after surgery in the radical group was significantly higher than that in the palliative group (17.2% vs. 5.2%, P=0.039). In terms of postoperative complications, the incidence of grade 1-5 complications in the radical group was significantly higher than that in the palliative group (37.9% vs. 15.5%, P=0.006); however, there was no significant difference in the incidence of grade 3-5 complications between the two groups (6.9% vs. 1.7%, P=0.364). In addition, the complications were subclassified, and it was found that the incidence of gastrointestinal disorders (20.7% vs. 6.9%, P=0.031) after surgery was significantly higher in the radical group. The 3-year OS rates were 55.2% and 22.6% in the radical and palliative groups, respectively (P<0.001). Multivariate analysis revealed that radical surgery was an independent prognostic factor for OS (HR: 4.32; 95% CI, 1.93-12.45; P<0.001). Conclusion Although elderly colorectal cancer patients over 80 years of age with intestinal obstruction are more likely to be admitted to the ICU and develop more postoperative complications after radical surgery, long-term survival benefits can be achieved.